Diet selection is related to breeding status in two frugivorous hornbill species of Central Africa. (23rd June 2014) - Lamperti, Aaron M.; French, Aaron R.; Dierenfeld, Ellen S.; Fogiel, Mark K.; Whitney, Kenneth D.; Stauffer, Donald J.; Holbrook, Kimberly M.; Hardesty, Britta D.; Clark, Connie J.; Poulsen, John R.; Wang, Benjamin C.; Smith, Thomas B.; et al.
Abstract: Avian diet selection is hypothesized to be sensitive to seasonal changes in breeding status, but few tests exist for frugivorous tropical birds. Frugivorous birds provide an interesting test case because fruits are relatively deficient in minerals critical for reproduction. Here, we quantify annual patterns of fruit availability and diet for two frugivorous hornbill (Bucerotidae) species over a 5.5-y period to test for patterns of diet selection. Data from the lowland tropical rain forest of the Dja Reserve, Cameroon, are used to generate two nutritional indices. One index estimates the nutrient concentration of the diet chosen by Ceratogymna atrata and Bycanistes albotibialis on a monthly basis using 3165 feeding observations combined with fruit pulp sample data. The second index is an estimate of nutrient concentration of a non-selective or neutral diet across the study area based on tree fruiting phenology, vegetation survey and fruit-pulp sample data. Fifty-nine fruit pulp samples representing 40 species were analysed for 16 nutrient categories to contribute to both indices. Pulp samples accounted for approximately 75% of the observed diets. The results support expected patterns of nutrient selection. The two hornbill species selected a diet rich in calcium during the early breeding season (significantly so for B. albotibialis in July and August). Through the brooding and fledging periods, they switched from a calcium-rich diet to one rich in iron and caloric content as well as supplemental protein in the form of invertebrates. Calcium, the calcium to phosphorus ratio and fat concentration were the strongest predictors of breeding success (significant for calcium and Ca:P for B. albotibialis in June). We conclude that hornbills actively select fruit based on nutritional concentration and mineral concentration and that the indices developed here are useful for assessing frugivore diet over time.